Ekonomi Berbasis Budaya Lokal: Adaptasi Masyarakat Cianjur Selatan Dalam Sistem Ekonomi Indonesia - Aludin Aludin; Sandi Setiadi (PT. Alahyan Publisher Sukabumi, 2025)
The development of an increasingly open global economic system requires local communities to adapt without losing their social and cultural identities. This study aims to analyze the role of a local culture-based economy as an adaptive mechanism for communities in the South Cianjur region in responding to the transformation of Indonesia’s economic system. Using a quantitative approach with an explanatory research design, data were collected from 120 respondents through purposive sampling. Data analysis was conducted using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The results indicate that local wisdom has a positive and significant influence on the formation of a culture-based economy as well as on community economic adaptation. The main findings reveal that a culture-based economy acts as a strong mediating variable linking traditional values with community survival strategies. Local wisdom, including mutual cooperation values and traditional knowledge, serves as crucial social capital in strengthening household economic resilience amid infrastructure limitations. This study concludes that strengthening an economy rooted in local identity is essential for achieving inclusive and sustainable regional development. National economic development policies should integrate local wisdom as an adaptive economic system to prevent rural communities from being marginalized by industrialization.